2020
DOI: 10.1021/acs.joc.0c01444
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on the Mechanism and Origin of the Different Regioselectivities of Manganese Porphyrin-Catalyzed C–H Bond Hydroxylation and Amidation of Equilenin Acetate

Abstract: The manganese porphyrin-catalyzed C−H bond hydroxylation and amidation of equilenin acetate developed by Breslow and his co-worker have been investigated with density functional theory (DFT) calculations. The hydroxylation of C(sp 2 )−H bond of equilenin acetate leading to the 6-hydroxylated product is more favorable than the hydroxylation of C(sp 3 )−H bond of equilenin acetate, leading to the 11β-hydroxylation product. The computational results suggest that the C(sp 2 )−H bond hydroxylation of equilenin acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…As shown in Figure 1 , the basic reaction pathway is similar to previous work of metalloporphyrin‐catalyzed C−H aminations,[ 6a , 11b , 11c , 12a ] having first nitrene formation and then nitrene transfer (C−H amination) steps. It should be noted that the general reaction pathway feature described here is the same no matter there is no ligand, negatively charged ligands with different coordination atoms, or neutral ligand.…”
Section: Resultssupporting
confidence: 68%
“…As shown in Figure 1 , the basic reaction pathway is similar to previous work of metalloporphyrin‐catalyzed C−H aminations,[ 6a , 11b , 11c , 12a ] having first nitrene formation and then nitrene transfer (C−H amination) steps. It should be noted that the general reaction pathway feature described here is the same no matter there is no ligand, negatively charged ligands with different coordination atoms, or neutral ligand.…”
Section: Resultssupporting
confidence: 68%
“…As shown in Figure 2, the general reaction pathway is similar to metalloporphyrin‐catalyzed C−H aminations [11e,15a,c,16a] and biocatalytic intermolecular C−H aminations [15b–d] . Clearly, the nitrene formation step with transition state TS1 is the overall RDS in the whole reaction pathway, consistent with experiment [1k] .…”
Section: Intramolecular C−h Aminationssupporting
confidence: 72%
“…Geometries of intermediates and transition states were optimized at the (U)­B3LYP-D3­(BJ)/BSI level in the acetonitrile/dichloromethane solvent with the SMD continuum solvation model, where BSI denotes the mixed basis set of LanL2DZ for the Mn atom and 6–31G­(d,p) for other atoms. In previous reports, it has been confirmed that the B3LYP functional shows a satisfactory performance for describing manganese/iron-based catalytic systems. ,, Harmonic vibrational frequency calculations were performed for all optimized geometries at the same level to confirm whether they are local minima or transition states and to obtain thermochemical corrections and Gibbs free energy. Intrinsic reaction coordinate (IRC) calculations were performed to determine that all transition states connect to their precursors and products.…”
Section: Computational Detailsmentioning
confidence: 96%